Maximizing the use of food emulsifiers - Baker, Steven R. (Kansas State University, 2010)
Emulsifiers have been and remain highly functional ingredients in the food industry. Emulsifiers contain both hydrophilic and lipophilic parts, resulting in their ability to be useful in foods at very low levels. However, knowledge of why emulsifiers work and how to use them most effectively is reserved for the few scientists who specialize in the discipline. Therefore, a comparison of current emulsifier theory with known emulsifier usage in the industry is beneficial to all who use these ingredients. Current emulsifier theory effectively describes how emulsifiers behave in food systems. Emulsion theory details how emulsifiers facilitate the formation and stability of emulsions through study of the kinetics of food systems. Emulsion theory further relates the ability of emulsifiers to interact with other substances in a food system. The main interactions concerning emulsifiers are their ability to form mesophases with water, to strengthen or weaken protein interactions, to form complexes with starches, and to promote or subdue fat crystallization. However, industrial applications of emulsifiers indicate areas where exceptions to theory exist. While emulsion theory has been found to effectively describe the individual interactions and functions in food, the simplicity of the models indicates that complex food system models are still needed to truly understand how to maximize the functionality of emulsifiers.
Keywords: Emulsifiers; Functionality; Monoglycerides; Mesophases; Agriculture, Food Science and Technology (0359)